Politik Hukum Adat dalam Pelestarian Tradisi Kawin Cai di Desa Maniskidul Kuningan - Iman Rifa'i (CV Rewang Rencang, 2025)
This study aims to analyze the legal politics of customary law in preserving the Kawin Cai tradition in Maniskidul Village, Kuningan Regency. Kawin Cai is a Sundanese traditional ceremony with a sacred meaning, symbolizing gratitude for water sources and maintaining harmony between humans and nature. In the national legal system, customary law is recognized under Article 18B(2) of the 1945 Constitution; however, its implementation faces challenges due to tourism village policies that lean towards commercialization. This research employs a normative juridical method with a statutory approach and document analysis. The findings indicate that customary law plays a crucial role in maintaining the social and spiritual legitimacy of the Kawin Cai tradition, while local legal politics should serve as an instrument for legal protection rather than merely a tool for tourism development. This study recommends the establishment of more specific regional regulations to ensure the sustainability and authenticity of Kawin Cai in the face of modernization.